Faceted and defect-rich CuMn2O4 nanoparticles for efficient electrochemical water splitting - Rani, Balasubramanian Jansi; Sivanantham, Arumugam; Shridharan, Tatachari Santhanagopalan; Runfa, Tan; Cho, In Sun (Journal of Materials Chemistry A, 2022)
Facet engineering, which exposes desired crystal planes, is an effective method for manipulating the surface adsorption and catalytic reactivity of electrocatalysts used in water splitting. Herein, we report the synthesis of faceted CuMn2O4 (f-CMO) nanoparticles via polyol-mediated annealing, in which ethylene glycol plays a crucial role in the formation of phase-pure and faceted CMO. We found that f-CMO has many facets, oxygen vacancies, and high electrical conductivity. Hence, its electrocatalytic water splitting activity was investigated to elucidate the impact of facet formation. Significantly, the f-CMO electrode exhibited superior hydrogen evolution reaction activity (overpotential: 116 mV and Tafel slope: 115 mV/dec) than non-f-CMO (239 mV and 163 mV/dec) at −10 mA cm−2 in 1 M KOH. Furthermore, it outperforms the reported spinel oxides at high current densities. Our results demonstrated that controlling the facet formation and particle size is essential for the development of efficient electrocatalysts for use in water splitting.
Keywords: Catalytic reactivity; Crystal planes; Electrocatalytic; Electrochemicals; Facet formation; High electrical conductivity; Hydrogen evolution reaction activities; Phase pure; Surface adsorption; Water splitting